GA Based Model for Real Time Dispatching in Silterra-An Approach to Dispatcher Optimization - Sathasivam, Renetha Malar (2008)
Real time dispatching in semiconductor manufacturing environment is indeed a critical process. Dispatching itself plays a critical role to determine the success of higher throughput and to achieve minimum cycle time. Dispatching is needed to improve production efficiencies by providing a scheduled and planned way of executing the manufacturing operational procedures. This research uses real time problem experienced by SilTerra Malaysia Sdn. Bhd. Real time dispatching requires rule to execute within seconds, but with SilTerra Dispatch List, current small rules take more than 10 seconds to execute. Since this takes time, most of the manufacturing technicians tend to switch over to the conventional way of lot dispatching by using FactoryWorks. This research proposes a GA model to optimize the use of dispatcher; which is used for real time dispatching. The result of this research concludes that GA approach can be greatly useful in optimizing dispatchers for Real Time Dispatching in the semiconductor industry.